Activation-induced Cell Death Drives Profound Lung CD4 + T-Cell Depletion in HIV-associated Chronic Obstructive Pulmonary Disease - Popescu, Iulia; Drummond, M. Bradley; Gama, Lucio; Coon, Tiffany; Merlo, Christian A.; Wise, Robert A.; Clements, Janice E.; Kirk, Gregory D.; McDyer, John F. (American journal of respiratory and critical care medicine, 2014)
As overall survival improves, individuals with HIV infection become susceptible to other chronic diseases, including accelerated chronic obstructive pulmonary disease (COPD). To determine whether individuals with HIV-associated COPD exhibit dysregulated lung mucosal T-cell immunity compared with control subjects. Using flow cytometry, we evaluated peripheral blood and lung mucosal T-cell immunity in 14 HIV(+)COPD(+), 13 HIV(+)COPD(-), and 7 HIV(-)COPD(+) individuals. HIV(+)COPD(+) individuals demonstrated profound CD4(+) T-cell depletion with reduced CD4/CD8 T-cell ratios in bronchoalveolar lavage-derived lung mononuclear cells, not observed in peripheral blood mononuclear cells, and diminished CD4(+) T cell absolute numbers, compared with control subjects. Furthermore, HIV(+)COPD(+) individuals demonstrated decreased pulmonary HIV-specific and staphylococcal enterotoxin B-reactive CD4(+) memory responses, including loss of multifunctionality, compared with HIV(+)COPD(-) control subjects. In contrast, lung mucosal HIV-specific CD8(+) T-cell responses were preserved. Lung CD4(+) T cells from HIV(+)COPD(+) individuals expressed increased surface Fas death receptor (CD95) and programmed death-1, but similar bronchoalveolar lavage viral loads as control subjects. However, programmed death-1 expression inversely correlated with HIV-specific lung CD4(+)IFN-γ(+) T-cell responses, suggesting functional exhaustion. Moreover, lung CD4(+) T cells from HIV(+)COPD(+) patients demonstrated increased basal and HIV antigen-induced expression of the early apoptosis marker annexin V compared with control subjects, which was significantly attenuated with anti-Fas blockade. Lastly, lung mucosal, but not blood, CD4(+)/CD8(+) ratios from HIV(+) patients significantly correlated with the FEV1, but not in HIV(-)COPD(+) patients. Together, our results provide evidence for profound lung mucosal CD4(+) T-cell depletion via a Fas-dependent activation-induced cell death mechanism, along with impaired HIV-specific CD4(+) immunity as immunologic features of HIV-associated COPD.